New application of ground beetle chitosan or carboxymethylated ground beetle chitosan and natural polysaccharide / polyphenol / metal injectable hydrogel for treating MRSA infectious bone defects

Through the combination of chitosan with methacrylic anhydride-chondroitin sulfate and strontium ions, a multifunctional hydrogel with antibacterial and promotes bone repair is formed, which solves the problem of existing bone repair materials in the repair of infectious bone defects. Inadequately, efficient bone defect healing and safe treatment effects have been achieved.

CN119112937APending Publication Date: 2024-12-13CHENGDU UNIV OF TRADITIONAL CHINESE MEDICINE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411249982.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing bone repair materials are difficult to support the complex repair process of infectious bone defects, especially in stages such as antibacterial, immune regulation, angiogenesis and osteogenesis differentiation, resulting in poor repair ability and prone to recurrence, and high costs for allogeneic or autologous transplantation. Immune rejection and infection risk.

Method used

Natural polysaccharides/polyphenols/metal injectable hydrogels using chitosan or its carboxymethylated derivatives combined with methacrylic anhydride-chondroitin sulfate and strontium ions are formed by covalent composite and photocrosslinking. Hydrogels with antibacterial, anti-inflammatory, pro-angiogenic and osteogenic differentiation biological activity.

Benefits of technology

The hydrogel is rapidly formed under mild conditions, has good mechanical properties and biological activity, can effectively reduce the risk of infection in bone defect sites, promote healing, and requires only one dose, with appropriate degradation time and high safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119112937A_ABST
    Figure CN119112937A_ABST
Patent Text Reader

Abstract

The invention provides an application of ground beetle chitosan or carboxymethylated ground beetle chitosan in preparation of a medicine for treating infectious bone defects. The invention further provides the carboxymethylated chlorogenic acid ground beeltle chitosan, a preparation method of the carboxymethylated chlorogenic acid ground beeltle chitosan and the natural polysaccharide / polyphenol / metal injectable hydrogel for treating MRSA infectious bone defects. The natural polysaccharide / polyphenol / metal in-situ injectable hydrogel prepared by the invention has good biological activities such as antibiosis, anti-inflammation, angiogenesis promotion, osteogenic differentiation and the like. The use dosage is small, a small amount of hydrogel can exert the drug effect, the patient compliance is good, the hydrogel reaches the bone defect part in an injection mode to exert the curative effect, and the risks of secondary infection and secondary injury to the bone defect part can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the use of Eupolyphaga sinensis chitosan or carboxymethyl Eupolyphaga sinensis chitosan in preparing a medicine for treating infected bone defects, and a natural polysaccharide / polyphenol / metal injectable hydrogel for treating MRSA infected bone defects. Background Art

[0002] In recent years, infected bone defects caused by trauma, tumors and other diseases have become a huge challenge in the global public health field due to their complex and long course, high infection recurrence rate and high disability rate, which has placed a great burden on patients' body and mind. The abuse of antibiotics has also led to the emergence of drug-resistant bacteria such as methicillin-resistant Staphylococcus aureus (MRSA), greatly increasing the difficulty of treating bacterial infections. Bacterial infection of bone defects can lead to insufficient local blood supply, reduced osteoblast differentiation, decreased bone regeneration ability and many other unfavorable factors that hinder the bone repair process.

[0003] The repair of infected bone defects usually includes five stages: antibacterial, immune regulation, angiogenesis, osteogenic differentiation, and biomineralization. However, existing bone repair materials are difficult to support all of the above stages, resulting in poor repair ability and easy recurrence. Allogeneic or autologous transplantation, as another treatment method for bone repair, also has the risks of high treatment costs, immune rejection, low healing rate, and potential infection, resulting in unsatisfactory treatment results.

[0004] The ideal material for treating infected bone defects should have good biocompatibility, antibacterial, anti-inflammatory properties, and the ability to promote the healing of bone defects. It should also reduce secondary damage to the bone defect and bacterial infection. Therefore, it is urgent to develop a new multifunctional material for treating infected bone defects.

[0005] Application No. 202210945658.4, Invention Name: A gel material for intra-articular injection and a preparation method thereof, discloses a gel material for intra-articular injection and a preparation method thereof, comprising the following steps: (1) dissolving an appropriate amount of carboxymethyl chitosan powder in deionized water to obtain a carboxymethyl chitosan solution with a concentration of 2%-5%; (2) adding chondroitin sulfate magnesium powder to the carboxymethyl chitosan solution, and stirring it at 30-50°C to make the system contain chondroitin sulfate magnesium The concentration is 50-200μg / mL; (3) the mixed solution obtained in step (2) is stirred and reacted with a cross-linking agent under a reaction condition of 30-50°C for 2-6h, and the concentration of the cross-linking agent is 1-2mg / L to obtain a cross-linked carboxymethyl chitosan hydrogel containing chondroitin sulfate magnesium. The chondroitin sulfate magnesium carboxymethyl chitosan hydrogel of the present invention can be used to prepare a gel product with the effects of inhibiting inflammation, filling articular cartilage defects, delaying chondrocyte apoptosis and promoting articular cartilage repair. The hydrogel prepared by this method needs to be generated at 30-50° C. The hydrogel reported in this patent has no antibacterial effect and cannot be used to treat infected bone defects, and there is no report that it can be used to treat MRSA infected bone defects.

[0006] Eupolyphaga sinensis Walker chitosan is the first product extracted and separated by the applicant from the Chinese medicine Eupolyphaga sinensis Walker. It has better antibacterial activity than commercial chitosan. In addition, studies have reported that compared with commercial shrimp and crab chitosan, insect chitosan has no seasonality, regionality, or allergy problems, and can become another major source of chitosan. At present, the chitosan we prepared has successfully prepared a variety of new dosage forms (nano electrospinning membranes, hydrogels, and nano sponges) for the healing of infectious wounds. (Multifunctional polysaccharide / metal / polyphenol double cross-linked hydrogel for infected wounds DOI:10.1016 / j.carbpol.2024.121912, Extraction and characterization of earthworm chitosan and its application in the preparation of electrospun nanofiber membranes DOI:10.1016fcolsurfb.2022.113030, Insect chitosan / pullulan / gallium photo-cross-linked hydrogel with multiple biological activities promotes the healing of MRSA-infected wounds DOI:10.1016 / j.carbpol.2024.122045, ZnMOF in situ embedded insect chitosan / pullulan / citric acid three-dimensional electrospun nanofiber sponge promotes the healing of MRSA-infected wounds DOI:10.1016 / j.cej.2024.155388). There is no literature report on the use of earthworm chitosan or carboxymethylated earthworm chitosan for the treatment of infected bone defects. Summary of the invention

[0007] One of the purposes of the present invention is to solve the technical deficiencies of the existing treatment of infected bone defects and provide a new use of Eupolyphaga sinensis chitosan. Another purpose of the present invention is to provide a safe and effective natural polysaccharide / polyphenol / metal in situ injectable hydrogel for treating infected bone defects.

[0008] The invention provides use of Eupolyphaga sinensis chitosan or carboxymethyl Eupolyphaga sinensis chitosan in preparing a medicine for treating infectious bone defects.

[0009] Wherein, the medicine is a medicine for treating MRSA-infected bone defects.

[0010] Wherein, the drug is a topical drug delivery preparation.

[0011] The present invention provides a carboxymethylated chlorogenic acid Eupolyphaga chitosan, which is a covalent complex prepared from carboxymethylated Eupolyphaga chitosan and chlorogenic acid as raw materials, and has the structural formula:

[0012]

[0013] The present invention provides a method for preparing carboxymethylated chlorogenic acid Eupolyphaga sinensis chitosan, which comprises the following steps:

[0014] a. Synthesis of carboxymethylated Eupolyphaga sinensis chitosan (ECCS):

[0015] The chitosan of Eupolyphaga sinensis and NaOH are added to isopropanol, and the mixture is expanded and alkalized at 25°C; chloroacetic acid is dissolved in isopropanol, and the mixture is added dropwise to the chitosan mixture of Eupolyphaga sinensis, and after stirring at 50°C for 3 hours, ethanol is added to stop the reaction, and the solid is obtained by filtration; then, the mixture is washed with 80% ethanol, desalted and dehydrated until the pH of the filtrate is neutral, and vacuum dried at 100°C overnight to obtain carboxymethylated chitosan of Eupolyphaga sinensis (ECCS);

[0016] b. Synthesis of carboxymethylated chlorogenic acid Eupolyphaga sinensis chitosan (ECCS-CA):

[0017] ECCS was slowly dispersed in pure water and stirred at room temperature overnight to obtain a uniform ECCS dispersion; chlorogenic acid and EDC·HCl (1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride) were dissolved in anhydrous ethanol, 6mmolNHS (N-hydroxysuccinimide) was added to the solution, the mixture was stirred, and then gradually added to the ECCS dispersion; the pH value was adjusted to 6.5, and the reaction was carried out at room temperature (150rpm) for 8 hours, and finally dialyzed with deionized water and freeze-dried to obtain an ECCS-CA covalent complex.

[0018] The invention provides a natural polysaccharide / polyphenol / metal injectable hydrogel for treating MRSA-infected bone defects, which is composed of the carboxymethylated chlorogenic acid Eupolyphaga chitosan, methacrylic anhydride-chondroitin sulfate, strontium ion (Sr 2+ ), wherein each mL contains: 70 mg of carboxymethylated chlorogenic acid Eupolyphaga chitosan, 50-130 mg of methacrylic anhydride-oxidized chondroitin sulfate, and strontium ions (Sr 2+ ) concentration 5-40mg.

[0019] More preferably, each mL contains: 70 mg of carboxymethylated chlorogenic acid Eupolyphaga chitosan, 100 mg of methacrylic anhydride-oxidized chondroitin sulfate, and 100 mg of strontium ion (Sr 2+ ) concentration 20mg.

[0020] Wherein, the preparation method of methacrylic anhydride-chondroitin sulfate comprises the following steps:

[0021] a. Synthesis of acrylic anhydride-chondroitin sulfate (CS-MA):

[0022] Take chondroitin sulfate and dissolve it in 50% dimethyl sulfoxide solution, add it into the 50% dimethyl sulfoxide solution containing chondroitin sulfate according to the ratio of sodium hydroxide (g): methacrylic anhydride (MA) = 3g: 9.97mL; adjust the pH to about 8 with sodium hydroxide solution, and react at 25°C in the dark for 48 hours; put the product into a dialysis bag (MWCO = 3500Da), dialyze it with deionized water, and then freeze-dry it to obtain methacrylic anhydride-chondroitin sulfate CS-MA;

[0023] b. Synthesis of methacrylic anhydride-oxidized chondroitin sulfate (OCS-MA)

[0024] The CS-MA prepared in step a was dissolved in deionized water, sodium periodate was added after dissolution, and the mixture was reacted at 25° C. in the dark for 8 hours, and ethylene glycol was added to terminate the reaction; the product was placed in a dialysis bag (MWCO=3500Da), dialyzed with deionized water, and then freeze-dried to obtain methacrylic anhydride-oxidized chondroitin sulfate OCS-MA.

[0025] The present invention also provides a method for preparing the natural polysaccharide / polyphenol / metal injectable hydrogel for treating MRSA-infected bone defects, which comprises the following steps:

[0026] a. Weigh the raw materials of each weight;

[0027] b. Dissolve ECCS-CA in deionized water and dissolve SrCl2 in deionized water and mix well;

[0028] c. Dissolve OCS-MA in PBS and mix it with the solution in step b to prepare a hydrogel.

[0029] The invention also provides use of the hydrogel in preparing a medicine for treating MRSA-infected bone defects.

[0030] The preparation method of the hydrogel of the present invention has mild conditions and short reaction time, and the hydrogel can be formed in only about 1 minute. The C / O / Sr / UV hydrogel of the present invention has better physical properties: the degradation time is relatively slow, only one administration is required, and the subsequent degradation time is similar to the course of the disease, there is no problem of difficult degradation, no toxic cross-linking agent is used, only natural ingredients are used, and clinical use is safer.

[0031] The natural polysaccharide / polyphenol / metal in situ injectable hydrogel prepared by the present invention has good biological activities such as antibacterial, anti-inflammatory, angiogenesis-promoting, osteogenic differentiation, etc. The dosage is small, a small amount of hydrogel can exert the drug effect, the patient compliance is good, and the injection method reaches the bone defect site to exert the therapeutic effect, which can reduce the risk of secondary infection and re-injury to the bone defect site. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 (A) Synthesis route of ECCS-CA (B) Synthesis route of OCS-MA;

[0033] Figure 2 (A) FT-IR images of ECS, ECCS and ECCS-CA (B) FT-IR images of CS, CS-MA and OCS-MA (C) 1 H NMR spectra of (D) CS, CS-MA and OCS-MA 1 H NMR spectra;

[0034] Figure 3 (A) Vial inversion experiment (B) C / O / Sr / UV hydrogel injectability experiment (C) C / O / Sr / UV hydrogel self-healing experiment (D) C / O / Sr / UV hydrogel adheres to different surfaces (paper, iron, glass, plastic);

[0035] Figure 4 Optical images of colonies after co-culture of C / O / Sr / UV hydrogel with Staphylococcus aureus, Escherichia coli, and MRSA;

[0036] Figure 5 (A) Live-dead staining of MC3T3-E1 cells (B) Cytoskeleton staining of MC3T3-E1 cells (C) HUVEC cell migration assay (C) ALP staining of BMSC cells;

[0037] Figure 6 Micro-CT images of rat leg bones treated with C / O / Sr / UV hydrogel for 4 and 7 weeks. DETAILED DESCRIPTION

[0038] Example 1 Preparation of the hydrogel of the present invention

[0039] 1. Synthesis and characterization of carboxymethylated chlorogenic acid Eupolyphaga chitosan (ECCS-CA), methacrylic anhydride-oxidized chondroitin sulfate (OCS-MA), and preparation and characterization of C / O / Sr / UV hydrogel

[0040] 1.1 Synthesis of carboxymethylated Eupolyphaga sinensis chitosan (ECCS)

[0041] 2 g ECS ​​(Echinochloa crusgalli chitosan) and 2.7 g NaOH (sodium hydroxide) were added to isopropanol (20 mL) and expanded and alkalized at 25°C for 3 hours. Then, chloroacetic acid (3 g) was dissolved in isopropanol (4 mL) and added dropwise to the previous mixture for 30 minutes. After stirring for 3 hours at 50°C, ethanol (50 mL) was added to stop the reaction and the solid was filtered. Then, the solid was rinsed with 80% ethanol several times, desalted and dehydrated until the filtrate pH was neutral, and vacuum dried at 100°C overnight.

[0042] 1.2 Carboxymethylated chlorogenic acid Eupolyphaga sinensis chitosan (ECCS-CA)

[0043] ECCS (4.0 g) was slowly dispersed in 100 mL of pure water and stirred at room temperature overnight to obtain a uniform ECCS dispersion. Then 3 mmol CA (chlorogenic acid) (1.06 g) and 6 mmol EDC·HCl (1-ethyl-(3-dimethylaminopropyl) carbodiimide hydrochloride) (1.15 g) were dissolved in 25 mL of anhydrous ethanol, and 6 mmol NHS (N-hydroxysuccinimide) (0.69 g) was further added to the solution. The mixture solution was stirred for 1 hour and then gradually added to the ECCS dispersion. The pH value of the resulting solution was adjusted to 6.5 using 1% acetic acid solution. The obtained solution was reacted at room temperature (150 rpm) for 8 hours. Thereafter, the sample was dialyzed with deionized water and freeze-dried to obtain an ECCS-CA covalent complex.

[0044] Among them, the process of preparing ECCS-CA is divided into two steps: carboxymethylation of ECS to ECCS and grafting of ECCS with chlorogenic acid.

[0045] The purpose of ECS carboxylation to ECCS is:

[0046] ① Pure chitosan (including ECS) is not soluble in water and can only be dissolved in water under acidic conditions, which will limit the scope of use. In addition, acidic conditions are not conducive to the healing of bone defects. Therefore, ECS is carboxymethylated.

[0047] ② Pure chitosan has amino groups and is positively charged, while chondroitin sulfate has sulfate groups and is negatively charged. When the two are mixed, precipitation will occur due to electrostatic effects, making it difficult to form a stable hydrogel. Carboxymethyl chitosan will greatly reduce the positive charge of chitosan, making it a stable hydrogel.

[0048] The purpose of grafting chlorogenic acid on ECCS: Chlorogenic acid is a natural ingredient extracted from traditional Chinese medicine, which has natural activities such as anti-inflammatory and antibacterial. After grafting chlorogenic acid, ECCS-CA has good antibacterial and antioxidant capabilities, which can reduce inflammation at the bone defect site, promote healing, and inhibit bacterial growth to prevent further infection.

[0049] 1.3 Synthesis of methacrylic anhydride-chondroitin sulfate (CS-MA)

[0050] Weigh 20g CS and dissolve it in 200mL 50% DMSO (dimethyl sulfoxide) solution, and add it in the ratio of sodium hydroxide (g): methacrylic anhydride (MA) = 3g: 9.97mL. Use 4mol / L sodium hydroxide solution to adjust the pH to about 8, and react at 25°C in the dark for 48 hours. Put the product in a dialysis bag (MWCO = 3500Da), dialyze it with deionized water, and then freeze-dry it to obtain CS-MA.

[0051] 1.4 Synthesis of methacrylic anhydride-oxidized chondroitin sulfate (OCS-MA)

[0052] 2 g CS-MA was dissolved in 40 mL deionized water, 1.32 g sodium periodate was added after dissolution, and the mixture was reacted at 25° C. in the dark for 8 hours, and ethylene glycol was added to terminate the reaction. The product was placed in a dialysis bag (MWCO=3500 Da), dialyzed with deionized water, and then freeze-dried to obtain OCS-MA.

[0053] Among them, after chondroitin sulfate is grafted with methacrylic anhydride groups, it has photo-crosslinking groups, which can be formed into photo-crosslinked hydrogels by adding photoinitiators and then irradiating with ultraviolet light. The mechanical properties of photo-crosslinked hydrogels will be better (in layman's terms, harder), closer to the hardness of bones, and can protect bone defects from external damage.

[0054] The ortho-hydroxyl groups of chondroitin sulfate are oxidized by sodium periodate to generate aldehyde groups, which can react with amino groups to form hydrogels. Dynamic Schiff base bonds can make hydrogels flexible, injectable and self-healing.

[0055] Preparation of 1.5C / O / Sr / UV hydrogel

[0056] Dissolve 70 mg ECCS-CA in 1 mL deionized water and dissolve SrCl2 in deionized water at a concentration of 20 mg / mL. Take 1 mL of ECCS-CA and 50 μL of SrCl2 solution and mix them evenly. Dissolve 100 mg OCS-MA in 1 mL PBS, take 0.8 mL of OCS-MA solution and mix with ECCS-CA / Sr to prepare hydrogel. Add 0.1% (w / v) LAP to the hydrogel and irradiate with UV light for 30 seconds to obtain C / O / Sr / UV hydrogel.

[0057] Strontium ions are added to the gel of the present invention, and the strontium ions have multiple biological activities: anti-inflammatory, angiogenesis-promoting, osteogenesis, etc. Strontium ions can also form metal coordination bonds with the catechol structure of chlorogenic acid, and can also enhance the mechanical properties and biological activity of the hydrogel.

[0058] The raw material synthesis route of the present invention is as follows Figure 1 shown.

[0059] Example 2 Screening test of preparation process conditions of the present invention

[0060] According to the preparation method of Example 1, the concentration of ECCS-CA, OCS-MA, illumination time and Sr 2+ Dosage, results are shown in the table:

[0061] Table 1 C / O / Sr / UV hydrogel condition screening (ECCS-CA concentration screening)

[0062]

[0063] By fixing the amount of OCS-MA, Sr 2+ The concentration of ECCS-CA was screened by adjusting the dosage and illumination time. Finally, the mechanical properties of the formed C / O / Sr / UV hydrogel were evaluated. The results showed that the C / O / Sr / UV hydrogel formed by ECCS-CA at a concentration of 7% had a moderate texture and was neither too hard nor too soft, which was suitable for the treatment and repair of bone defects.

[0064] Table 2 C / O / Sr / UV hydrogel condition screening (OCS-MA concentration screening)

[0065]

[0066] By fixing the amount of ECCS-CA, Sr 2+The concentration of OCS-CA was screened by dosage and illumination time. Finally, the concentration of OCS-MA was screened by mechanical properties and whether it could form C / O / Sr / UV hydrogel. The results showed that the C / O / Sr / UV hydrogel formed by OCS-MA at a concentration of 10% had a moderate texture and was neither too hard nor too soft, which was suitable for the treatment and repair of bone defects.

[0067] Table 3 C / O / Sr / UV hydrogel condition screening (light exposure time screening)

[0068]

[0069] By fixing the ECCS-CA dosage, OCS-MA dosage and Sr 2+ Finally, the illumination time was screened mechanically. The results showed that the C / O / Sr / UV hydrogel formed under 30s illumination had a moderate texture and was neither too hard nor too soft, which was suitable for the treatment and repair of bone defects.

[0070] Table 4 C / O / Sr / UV hydrogel conditions screening (Sr 2+ Dosage filter)

[0071]

[0072] By fixing the ECCS-CA dosage, OCS-MA dosage and illumination time, Sr 2+ Finally, the cell survival rate was used to evaluate Sr 2+ The results showed that the C / O / Sr / UV hydrogel formed under 20 mg / mL conditions can significantly promote cell proliferation and is suitable for the treatment and repair of bone defects.

[0073] After multiple screening, the final concentration of ECCS-CA was 7%, the concentration of OCS-MA was 10%, and the concentration of Sr 2+ The concentration is 20 mg / mL, and the illumination time is 30 seconds. That is, each mL contains: 70 mg of carboxymethylated chlorogenic acid Eupolyphaga chitosan, 100 mg of methacrylic anhydride-oxidized chondroitin sulfate, 20 mg of Sr ion concentration, and the illumination time is 30 seconds.

[0074] Example 3 Characterization of the raw materials and final products of the present invention

[0075] 1. Infrared spectroscopy (FT-IR)

[0076] Fourier transform infrared spectrometer (PerkinElmer, USA) was used to measure the carbonylation of ECS, ECCS, EECCS-CA, CS, CS-MA, OCS-MA and hydrogel at 4000-400 cm -1For the absorption peaks in the range, the amounts of sample and KBr were 5 mg and 150 mg, respectively, and the number of scans was 32.

[0077] 2. H NMR spectroscopy ( 1 H NMR)

[0078] The molecular weights of ECS, ECCS, EECCS-CA, CS, CS-MA and OCS-MA were determined using a Brucker 600 MHz NMR instrument (Brucker, Germany). 1 H NMR, the sample amount is 10 mg, the solvent amount is 1 mL. The solvent of ECS is 0.5% HCl (v:v) D2O solution, and the solvent of other samples is D2O. The chemical shift unit is ppm. Figure 2 shown.

[0079] 3. Characterization of C / O / Sr / UV hydrogel

[0080] The solution-gel transition at 37°C was determined by a vial inversion experiment. The gelation time was recorded by stopping the flow of the mixed solution when the test tube was inverted. The injectability of the hydrogel was tested by loading the hydrogel into a 2.5mL syringe (26G) and injecting it into a specific letter-shaped mold. The C / O / Sr / UV hydrogel stained with methylene blue was cut into multiple parts. The cut hydrogel interfaces were then brought into contact with each other at room temperature, and the self-healing process of the hydrogel was photographed and recorded. We attached the C / O / Sr / UV hydrogel to various objects to test its adhesion ability (such as Figure 3 shown).

[0081] The beneficial effects of the present invention are demonstrated by pharmacodynamic tests as follows.

[0082] Test Example 1 In vitro antibacterial test of the hydrogel of the present invention

[0083] Staphylococcus aureus (S. aureus), Escherichia coli (E. coli) and methicillin-resistant Staphylococcus aureus (MRSA) were used as model strains to evaluate the antibacterial properties of the hydrogel. 200 mg of sterilized hydrogel was mixed with 200 μL (1×10 6 CFU / mL) bacterial solution and 800 μL sterile liquid culture medium were co-cultured in 48-well plates for 12 h, and the in vitro antibacterial ability of C / O / Sr / UV hydrogels was evaluated by the dilution plate method (e.g. Figure 4 shown).

[0084] Experimental Example 2 In vitro cell experiment of hydrogel of the present invention

[0085] Cell culture: MC3T3-E1 cells were cultured in MEM complete medium containing 10% inactivated fetal bovine serum (FBS) and 1% PS, HUVEC cells were cultured in DMEM medium containing 10% inactivated fetal bovine serum (FBS) and 1% PS, and BMSC cells were cultured in α-MEM medium containing 10% inactivated fetal bovine serum (FBS) and 1% PS and placed in an incubator at 37°C, containing 5% CO2 (v / v) and cultured to 3-8 generations for subsequent experiments.

[0086] Take MC3T3-E1 cell suspension (1×10 5 / mL), directly co-cultured with sterilized C / O / Sr / UV hydrogel co-culture solution, and co-cultured in a confocal culture dish for a specified time. The co-cultured cells were stained with calcein-AM / PI live-dead cell staining, and the cell morphology and viability were directly observed using a fluorescence microscope.

[0087] In the cell proliferation assay, MC3T3-E1 cells were stained with phalloidin (iFluor 488phalloidin) and 4',6-diamidino-2-phenylindole (DAPI). The staining was performed as described. After the incubation period, the samples were gently washed three times with PBS. The stained cells were imaged using an inverted fluorescence microscope.

[0088] HUVEC cell migration assay was used to study the effect of hydrogel on cell migration ability. HUVEC cells in the logarithmic growth phase were collected and plated at 3×10 6 The cells were inoculated into 6-well plates at a concentration of 100 cells / well and cultured at 5% CO2 and 37°C until the cells occupied 80% of the space at the bottom of the culture dish. A straight line was drawn on the cell surface with a sterile pipette tip (outer diameter of about 0.8 mm) to simulate a wound, and then the cell debris was washed three times with PBS (pH = 7.4). 1 mL of DMEM complete medium was added to the blank group, and 1 mL of C / O / Sr / UV hydrogel co-culture solution was added to the C / O / Sr / UV hydrogel group. The culture was continued for 24 hours, and the migration of cells toward the wound was observed with an optical microscope, and photos were taken at 24 hours.

[0089] Alkaline phosphatase (ALP) detection was used to evaluate the osteogenic differentiation of C / O / Sr / UV hydrogel. Bone marrow mesenchymal stem cells were cultured at 5×10 4 The cells were inoculated into the upper layer of the cell membrane at a density of 10 cells / mL. After culturing in osteogenic medium for 7 and 14 days, the samples were rinsed with PBS and ALP working solution was added to each well to observe ALP staining. ALP activity was determined using an alkaline phosphatase detection kit (eg Figure 5 shown).

[0090] Experimental Example 3 Animal Experiment of the Hydrogel of the Present Invention

[0091] 48 SD rats (weight 220 to 240 g) were adapted to a standard diet for one week before the experiment. The rats were anesthetized with 2% sodium pentobarbital (60 mg / kg), the hair around the thighs was removed with a razor and depilatory cream, and a bone defect with a diameter of 1 mm was created on the leg bone of each rat. 50 μL of MRSA bacterial solution (1×10 8 CFU mL -1 ), and then the wound was sutured with medical sutures to establish a rat infection model of MRSA-induced bone defects. After the bacterial infection was successfully established, the C / O / Sr / UV hydrogel was injected into the bone defect and then cross-linked under UV light for 30 seconds. The rats were fed for 4 and 7 weeks, respectively, and in vivo micro-CT imaging was performed, and then the rats were euthanized and the leg bones were removed. In vitro micro-CT imaging was performed. Subsequently, the leg bones were decalcified and analyzed using hematoxylin and eosin (H&E) staining and Masson's trichrome staining. In addition, immunohistochemistry and immunofluorescence were performed on bone tissue to study the immunomodulatory, angiogenic, and osteogenic properties of the hydrogel (such as Figure 6 shown).

[0092] The C / O / Sr / UV hydrogel prepared by the present invention is a new type of three-crosslinked injectable hydrogel. Most injectable hydrogels are formed only by physical crosslinking or chemical crosslinking, and have defects such as poor mechanical properties and low activity, which greatly limits their application in bone repair. However, natural polysaccharide hydrogels with a variety of reticular structures can enhance the mechanical properties and biological activity of hydrogels from different aspects, and effectively promote bone repair. Adding metal ions strontium with antibacterial and anti-inflammatory properties to injectable hydrogels can not only enhance the mechanical properties and biological activity of injectable hydrogels, but also control the release rate of metal ions and improve the safety of metal ion use. Photo-crosslinked injectable hydrogels can be photo-crosslinked in situ, further improve mechanical properties and fit tightly with irregular bone defect sites to prevent falling off. Therefore, the multifunctional photo-crosslinked injectable hydrogel (C / O / Sr / UV hydrogel) prepared by natural polysaccharides and metal ions can not only enhance the mechanical properties, injectability and self-healing properties of hydrogels, but also provide a suitable microenvironment for bone repair and accelerate the healing of bone defect sites.

Claims

1. Use of Eupolyphaga sinensis chitosan or carboxymethyl Eupolyphaga sinensis chitosan in preparing a medicine for treating infectious bone defects.

2. The use according to claim 1, Features: The medicine is a medicine for treating MRSA infected bone defects.

3. The use according to claim 1 or 2, Features: The medicament is a topical drug delivery formulation.

4. A carboxymethylated chlorogenic acid Eupolyphaga sinensis chitosan, Features: It is a covalent complex prepared from carboxymethylated earthworm chitosan and chlorogenic acid, and its structural formula is:

5. The method for preparing the carboxymethylated chlorogenic acid Eupolyphaga sinensis chitosan according to claim 4, Features: It includes the following steps: a. Synthesis of carboxymethylated Eupolyphaga sinensis chitosan (ECCS): The chitosan of Eupolyphaga sinensis and NaOH are added to isopropanol, and the mixture is expanded and alkalized at 25°C; chloroacetic acid is dissolved in isopropanol, and the mixture is added dropwise to the chitosan mixture of Eupolyphaga sinensis, and after stirring at 50°C for 3 hours, ethanol is added to stop the reaction, and the solid is obtained by filtration; then, the mixture is washed with 80% ethanol, desalted and dehydrated until the pH of the filtrate is neutral, and vacuum dried at 100°C overnight to obtain carboxymethylated chitosan of Eupolyphaga sinensis (ECCS); b. Synthesis of carboxymethylated chlorogenic acid Eupolyphaga sinensis chitosan (ECCS-CA): ECCS was slowly dispersed in pure water and stirred at room temperature overnight to obtain a uniform ECCS dispersion; chlorogenic acid and EDC·HCl (1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride) were dissolved in anhydrous ethanol, 6 mmol NHS (N-hydroxysuccinimide) was added to the solution, the mixture was stirred, and then gradually added to the ECCS dispersion; the pH value was adjusted to 6.5, and the reaction was carried out at room temperature (150 rpm) for 8 hours, and finally dialyzed with deionized water and freeze-dried to obtain an ECCS-CA covalent complex.

6. A natural polysaccharide / polyphenol / metal injectable hydrogel for treating MRSA-infected bone defects, Features: The invention is composed of the carboxymethylated chlorogenic acid ground beetle chitosan as claimed in claim 4, methacrylic anhydride-oxidized chondroitin sulfate, strontium ion (Sr 2+ ) prepared from a hydrogel, wherein each mL contains: 70 mg of carboxymethylated chlorogenic acid earthworm chitosan, 50-130 mg of methacrylic anhydride-oxidized chondroitin sulfate, and 5-40 mg of Sr ion concentration.

7. The natural polysaccharide / polyphenol / metal injectable hydrogel for treating MRSA-infected bone defects according to claim 6, Features: Each mL contains: carboxymethylated chlorogenic acid Eupolyphaga chitosan 70 mg, methacrylic anhydride-oxidized chondroitin sulfate 100 mg, strontium ion (Sr 2+ )20mg.

8. The natural polysaccharide / polyphenol / metal injectable hydrogel for treating MRSA-infected bone defects according to claim 6 or 7, Features: The preparation method of methacrylic anhydride-chondroitin sulfate comprises the following steps: a. Synthesis of methacrylic anhydride-chondroitin sulfate (CS-MA): Take chondroitin sulfate and dissolve it in 50% dimethyl sulfoxide solution according to the ratio of sodium hydroxide (g): methacrylic anhydride (MA) = 3g: 9.97 mL was added to a 50% dimethyl sulfoxide solution containing chondroitin sulfate; the pH was adjusted to about 8 with sodium hydroxide solution, and the reaction was carried out at 25° C. in the dark for 48 hours; the product was placed in a dialysis bag (MWCO=3500Da), dialyzed with deionized water, and then freeze-dried to obtain acrylic anhydride-chondroitin sulfate CS-MA; b. Synthesis of methacrylic anhydride-oxidized chondroitin sulfate (OCS-MA) The CS-MA prepared in step a was dissolved in deionized water, sodium periodate was added after dissolution, and the mixture was reacted at 25° C. in the dark for 8 hours, and ethylene glycol was added to terminate the reaction; the product was placed in a dialysis bag (MWCO=3500Da), dialyzed with deionized water, and then freeze-dried to obtain methacrylic anhydride-oxidized chondroitin sulfate OCS-MA.

9. A method for preparing a natural polysaccharide / polyphenol / metal injectable hydrogel for treating MRSA-infected bone defects according to any one of claims 6 to 8, Features: It includes the following steps: a. Weigh the raw materials of each weight; b. Dissolve ECCS-CA in deionized water and add SrCl 2 Dissolve in deionized water and mix well; c. Dissolve OCS-MA in PBS and mix with the solution in step b to prepare a hydrogel.

10. Use of the hydrogel according to any one of claims 6 to 8 in the preparation of a medicament for treating MRSA-infected bone defects.